Pengaruh Dimensi Servqual terhadap Kepuasan Pasien di Apotek Rumah Sakit Stella Maris Makassar - Mutmainnah Mutmainnah; Grace Windiwulandari; Maria Aprilia Soge (Yayasan Literasi Sains Indonesia, 2026)
Patient satisfaction is a crucial indicator in evaluating the quality of healthcare services, including hospital pharmacy installations. Based on patient feedback at the Stella Maris Hospital Pharmacy in Makassar, complaints were identified regarding long waiting times, lack of drug information, and the absence of a clear queue information system, which could potentially decrease patient satisfaction. This study aims to evaluate the effect of service quality using the SERVQUAL approach (tangibles, reliability, responsiveness, assurance, and empathy) on patient satisfaction. This quantitative research used a cross-sectional design. Data were collected from 103 outpatients using validated and reliable questionnaires and analyzed via multiple linear regression analysis. The results showed that simultaneously, all SERVQUAL dimensions significantly influenced patient satisfaction (F = 16.765, p = 0.000). Partially, only reliability (p = 0.013) and empathy (p = 0.000) had a significant positive effect, with empathy being the most dominant factor (Beta = 0.546). Responsiveness, assurance, and tangibles did not show significant effects. In conclusion, patient satisfaction is heavily driven by staff empathy and service reliability. Pharmacies should focus on interpersonal communication training and service accuracy to optimize patient experiences.